2013
DOI: 10.1155/2013/801530
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Cognitive Empathy in First-Year Medical Students

Abstract: Objectives. Doctors' empathy towards their patients is considered important for treatment outcome. However, during medical school there might be a decline in empathy called “hardening of the heart.” This study evaluated the cognitive and emotional empathy in medical students and investigated the influence of a preference for a specialty and students attachment styles. Methods. 126 first-year medical students were included and completed the Reading the Mind in the Eyes Test revised version (RME-R), the Balanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
(19 reference statements)
1
14
0
2
Order By: Relevance
“…Paradoxically, however, students report being overloaded with activities, and burdened with constant stress and a sense of competition. According to some research, medical students also show low emotional and cognitive empathy scores, and an avoidant attachment style [35]. This may increase burnout and decrease the ability to connect with patients [36].…”
Section: Medical Studentsmentioning
confidence: 99%
“…Paradoxically, however, students report being overloaded with activities, and burdened with constant stress and a sense of competition. According to some research, medical students also show low emotional and cognitive empathy scores, and an avoidant attachment style [35]. This may increase burnout and decrease the ability to connect with patients [36].…”
Section: Medical Studentsmentioning
confidence: 99%
“…For this reason, we planned a second experiment in which we assessed other aspects that might be important in determining proficiency in understanding social emotions. Similar to the studies on empathy performed by (Dehning et al, 2013 , 2014 ), in which the authors took into account professional choice hypothesizing that surgeons are less empathetic than psychiatrists (Dehning et al, 2014 ), we considered artistic attitude. We hypothesized that artists would be more empathetic and also more able to understand social emotions than non artists of the same age and the same level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Other individual differences are related to personality traits that drive people in choosing a profession. Specifically, a study found that surgeons are less empathetic than psychiatrists (Dehning et al, 2013 ). Moreover, another study found that higher levels of empathy drive the choice of first-year medical students and their preference for a specialty with continuous patient care (Dehning et al, 2014 ).…”
mentioning
confidence: 99%
“…The assumption is that Socratic styles are not compatible with empathy development. To support this, one study observed that physician empathy tended to decrease as the physician became more professionally educated (Dehning et al, 2013). Actual interpersonal exchange benefits were confirmed in a study of weight loss for diabetic patients, and empathy practiced in an actual setting brought better client outcomes (Canale et al, 2012).…”
Section: A Training Modelmentioning
confidence: 99%